Clinical comparison of a xenogeneic collagen matrix versus subepithelial autogenous connective tissue graft for augmentation of soft tissue around implants. Issue 7 (July 2021) - De Angelis, P.; De Angelis, S.; Passarelli, P.C.; Liguori, M.G.; Pompa, G.; Papi, P.; Manicone, P.F.; D'Addona, A.
Abstract: Dental implant placement is a predictable therapy for replacing teeth. Nevertheless, mechanical, biological, and aesthetic complications frequently occur. The aim of this study was to compare the clinical outcomes of a xenogeneic collagen matrix (XCM) used at the time of implant placement as an alternative to a subepithelial connective tissue graft (SCTG), for soft tissue augmentation. This was a prospective clinical trial with 12 months of follow-up. In the control group, soft tissue augmentation at the time of implant placement was performed with a SCTG, while in the test group, a XCM was employed. At 12 months postoperative, all xenografts showed no postoperative complications. In both groups, a significantly greater thickness was observed on the buccal and occlusal sides from preoperative to 3 months postoperative ( P  < 0.05). No statistically significant difference in pink aesthetic score ( P  = 0.379, 6 months postoperative) or marginal bone loss ( P  = 0.449 at 3 months postoperative, P  = 0.778 at 6 months postoperative) was observed between the groups. Statistically significant differences in pain perceived by the patients ( P  < 0.0001) and the time to complete the surgical procedure ( P  = 0.0008) were detected. At 12 months after surgery, XCM provided similar clinical results in terms of soft tissue augmentation on the buccal and occlusal sides as compared with the SCTG.